Method for reducing polymer caking in olefin polymerization

By using alkyl zinc and catalysts during the olefin polymerization process and not using antistatic agents, the problem of polymer agglomeration is solved, and the catalyst activity and polymer yield are improved.

CN119775459APending Publication Date: 2025-04-08CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311295247.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-08
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the process of olefin polymerization, the prior art is difficult to effectively reduce the problem of polymer agglomeration, especially when using finished catalysts, the method of optimizing the catalyst is not applicable.

Method used

Olefin polymerization is carried out in the presence of alkyl zinc and catalyst, and no antistatic agent is used to reduce the agglomeration of the polymer and increase the activity of the catalyst.

Benefits of technology

Through this method, the agglomeration of the polymer can be effectively reduced, the activity of the catalyst can be improved, and the yield of the polymer can be increased, and the amount of cocatalyst can be reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004483279890000081
    Figure BDA0004483279890000081
Patent Text Reader

Abstract

The present invention relates to the technical field of olefin polymerization, and discloses a method for reducing polymer caking in olefin polymerization, the method comprises: carrying out olefin polymerization in the presence of zinc alkyl and a catalyst, and an antistatic agent is not used in the olefin polymerization process. According to the method, the zinc alkyl is added in the olefin polymerization process, so that the caking of the polymer can be effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of olefin polymerization, and in particular to a method for reducing polymer agglomeration in olefin polymerization. Background Art

[0002] Agglomeration is a common problem encountered in the production process of polyolefins. The occurrence of agglomeration may produce unqualified waste and reduce the quality of polymers at the least. At the worst, it may affect the long-term stable operation of the polyolefin plant and even cause abnormal shutdown.

[0003] The causes of agglomeration include catalyst agglomeration caused by problems in catalyst preparation, catalyst storage for too long or improper storage, and static electricity during the production process. Compared with ZN catalysts (Ziegler-Natta catalysts), static electricity generated by metallocene catalysts is more serious and difficult to predict, and sometimes it will suddenly occur after stable operation.

[0004] There are many methods to reduce agglomeration in the polymerization process in industry, mainly including catalyst optimization, catalyst prepolymerization, and adding antistatic agents to reduce agglomeration during the polymerization process. Antistatic agents include: polyols, alkyl diethanolamines, aluminum stearate, amines, polysulfones, alkyl sulfonic acids, sulfonates, quaternary ammonium salts, aziridine copolymers, and having the formula -(CH2-CH2-NJ) n -polyaziridine, etc. Commercially available antistatic agents include Irgastat AS-990 from Huntsman, Lupasol FG from BASF, ATMER series products from ICI America Inc. from Crompton Corporation, Octastat series products from Innospecinc., Statsafe series, and Synperonic PEL121 from Uniqema.

[0005] However, for catalysts purchased as finished products, such methods of catalyst optimization are not applicable. Summary of the invention

[0006] The object of the present invention is to overcome the problem of polymer product agglomeration in the prior art and provide a method for reducing polymer agglomeration in olefin polymerization.

[0007] The inventors of the present invention unexpectedly discovered that adding alkyl zinc in the olefin polymerization process without using an antistatic agent can not only reduce the content of large particles in the polymer product, but also improve the activity of the catalyst. In order to achieve the above object, the first aspect of the present invention provides the use of alkyl zinc in reducing olefin polymer agglomeration, characterized in that the use comprises: olefin polymerization in the presence of alkyl zinc and a catalyst; and no antistatic agent is used in the olefin polymerization process.

[0008] The second aspect of the present invention provides a method for reducing polymer agglomeration in olefin polymerization, the method comprising: conducting olefin polymerization in the presence of alkyl zinc and a catalyst; and not using an antistatic agent during the olefin polymerization process.

[0009] Through the above technical solution, the present invention achieves the following beneficial effects:

[0010] (1) Adding alkyl zinc during olefin polymerization using the method of the present invention can effectively reduce polymer agglomeration.

[0011] (2) Compared with the prior art, the present invention can achieve the effect of controlling the electrostatic level of the reactor without using an antistatic agent, and at the same time, can also reduce the amount of co-catalyst used.

[0012] (3) Compared with the prior art, the use of alkyl zinc in the present invention can not only reduce the agglomeration of the polymer, but also improve the activity of the catalyst, thereby increasing the yield of the polymer.

[0013] (4) Preferably, the alkyl zinc of the present invention can reduce polymer agglomeration, improve catalyst activity, and reduce the residual amount of alkyl zinc in the polymer when used in a relatively low amount, which is beneficial for preparing high-quality polymers. DETAILED DESCRIPTION

[0014] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0015] The first aspect of the present invention provides the use of alkyl zinc in reducing olefin polymer agglomeration, characterized in that the use comprises: conducting olefin polymerization in the presence of alkyl zinc and a catalyst; and no antistatic agent is used in the olefin polymerization process.

[0016] The second aspect of the present invention provides a method for reducing polymer agglomeration in olefin polymerization, the method comprising: conducting olefin polymerization in the presence of alkyl zinc and a catalyst; and not using an antistatic agent during the olefin polymerization process.

[0017] In the present invention, reducing polymer agglomeration in olefin polymerization mainly refers to reducing the proportion of polymer products with a particle size greater than 0.5 mm, so that the particle size of the polymer products is mainly concentrated in the range of less than 0.5 mm (preferably in the range of 0.07-0.25 mm). Preferably, the proportion of polymer particles less than 0.5 mm prepared by the present invention is more than 98%, and the proportion of polymer particles greater than 0.5 mm is less than 1.7% (more preferably less than 1%); the proportion of polymer particles distributed in the range of 0.07-0.25 mm is more than 95%. At the same time, reducing polymer agglomeration in olefin polymerization also means that there is basically no agglomeration, flaking, etc. on the reactor and reactor wall.

[0018] According to the present invention, preferably, the alkyl zinc is at least one of C2-C10 alkyl zincs, more preferably at least one of diethyl zinc, dimethyl zinc, dipropyl zinc and dibutyl zinc; further preferably diethyl zinc. In the present invention, C2-C10 alkyl zinc means that the carbon number of the alkyl group in the alkyl zinc is 2-10 (for example, 2, 3, 4, 5, 6, 7, 8, 9, 10).

[0019] According to the present invention, preferably, the olefin polymerization is carried out in a polymerization medium, and the alkyl zinc is added in an amount of 0.1ppm-1000ppm of the polymerization medium (for example, 0.1ppm, 1ppm, 100ppm, 200ppm, 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, and a range consisting of any two of the above points). In the present invention, "ppm" represents mass concentration, i.e. 1ppm=1mg 烷基锌 / 1L 聚合介质 .

[0020] According to the present invention, more preferably, the polymerization medium comprises an inert gas and / or a C3-C10 alkane. The inert gas may be at least one of nitrogen, helium, neon, argon and krypton. The C3-C10 alkane may be at least one of propane, butane, isobutane, pentane, isopentane and hexane.

[0021] According to the present invention, the catalyst can be a conventional olefin polymerization catalyst in the art, for example, the catalyst disclosed in CN109694424A and CN103087241A. Preferably, the catalyst is a supported catalyst, preferably at least one of a metallocene catalyst, a non-metallocene catalyst and a Ziegler-Natta catalyst; more preferably a supported metallocene catalyst.

[0022] According to the present invention, preferably, the metal element in the supported metallocene catalyst is at least one of the IVB elements, preferably at least one of Ti, Zr and Hf.

[0023] In the present invention, preferably, the supported metallocene catalyst comprises a bridged metallocene compound, an aluminoxane and a carrier. For example, the catalyst disclosed in CN103087241A can be used. More preferably, the bridged metallocene compound has a structure of CpXCpMQ2, wherein Cp is a metallocene ligand selected from a cyclopentadiene derivative group, the cyclopentadiene derivative group includes a cyclopentadienyl group, an indenyl group or a fluorenyl group, and the cyclopentadiene derivative group in the ligand may contain one or more substituents, and the substituents are selected from C1-C12 alkyl, alkoxy, silane, aryl or aralkyloxy groups; X is a bridging group, which may be a C1-C4 carbon bridge, a silicon bridge or a germanium bridge with a substituted alkyl or cycloalkyl group; M is selected from at least one of the IVB elements; Q is a halogen (e.g., chlorine element). More preferably, aluminoxane methylaluminoxane or modified methylaluminoxane. More preferably, the carrier comprises an inorganic carrier or an organic carrier, more preferably at least one of an inorganic oxide, an inorganic chloride and a polymer (for example, the carrier may be silica gel, Al2O3, MCl2, polystyrene, etc.). Further preferably, the molar ratio of the bridged metallocene compound to the aluminoxane is 0.0001-0.1:1 (preferably 0.002-0.05:1). Further preferably, the mass ratio of the aluminoxane to the carrier is 1:0.5-4.

[0024] According to the present invention, a co-catalyst may also be used in the olefin polymerization process. Preferably, the olefin polymerization further comprises the use of a co-catalyst, and the co-catalyst is an organic aluminum. Preferably, the organic aluminum is an alkyl aluminum. More preferably, the alkyl aluminum is selected from at least one of trimethyl aluminum, triethyl aluminum, tri-n-propyl aluminum, triisobutyl aluminum, tri-n-butyl aluminum, triisopentyl aluminum, tri-n-pentyl aluminum, tri-n-hexyl aluminum, triisohexyl aluminum, diethyl methyl aluminum and dimethyl ethyl aluminum.

[0025] According to the present invention, preferably, the molar ratio of the catalyst calculated as IVB element to the co-catalyst calculated as aluminum element is 1:10-5000 (e.g., 1:10, 1:100, 1:200, 1:400, 1:600, 1:800, 1:900, 1:1000, 1:1100, 1:1200, 1:1300, 1:1400, 1:1600, 1:1800, 1:2000, 1:3000, 1:4000, 1:5000, and ranges formed by any two of the above), more preferably 1:25-2000. For example, when the metal element in the metallocene catalyst is Zr element, the catalyst calculated as IVB element can be expressed as a catalyst calculated as Zr element.

[0026] According to the present invention, the type of the olefin is not particularly limited, and the olefin commonly used in the art can be used. Preferably, the olefin is ethylene and / or α-olefin; preferably, the α-olefin includes at least one of propylene, 1-butene, 1-pentene, 1-hexene and 1-octene. The olefin polymerization of the present invention can be olefin homopolymerization, such as polyethylene, polypropylene, etc.; it can also be olefin copolymerization, such as ethylene copolymerization (the comonomer can be α-olefin), propylene copolymerization (the comonomer can be ethylene or other α-olefins), etc.

[0027] According to the present invention, preferably, the conditions for olefin polymerization include: temperature 20-130°C, preferably 60-100°C; pressure 0.3-5MPa, preferably 0.5-3MPa. The temperature of olefin polymerization can be 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, and a range consisting of any two of the above; the pressure of olefin polymerization can be 0.3MPa, 0.8MPa, 1MPa, 1.1MPa, 1.2MPa, 1.5MPa, 2MPa, 3MPa, 4MPa, 5MPa, and a range consisting of any two of the above.

[0028] According to the present invention, preferably, the olefin polymerization is carried out in a slurry polymerization or a gas phase polymerization. More preferably, the olefin polymerization reaction is a slurry polymerization, and the solvent (polymerization medium) used in the slurry polymerization is preferably an alkane, such as at least one of hexane, propane, butane, isobutane, pentane and isopentane.

[0029] According to a particularly preferred embodiment of the present invention, the method comprises: purging the polymerization kettle with nitrogen, then injecting 5-6L of hexane, heating to 40-60°C, sequentially adding 5-10mmol of triisobutylaluminum, adding 5-10mmol (preferably 5-6mmol) of diethylzinc, 100-120mg of catalyst, and finally adding 0.5-1L of hexane to flush the catalyst pipeline, then heating the reactor, and after the temperature rises to 70-90°C, continuously adding ethylene to make the ethylene partial pressure 0.5-1.5MPa, and performing constant pressure reaction.

[0030] The present invention will be described in detail below by way of examples. Unless otherwise specified, all of the raw materials used below are commercially available.

[0031] Ethylene: polymerization grade, Beijing Huanyu Jinghui Jingcheng Gas Technology Co., Ltd.;

[0032] Comonomer: 1-hexene, polymerization grade, Sinopec Yanshan Branch;

[0033] Solvent: Hexane, analytical grade, J&K;

[0034] Hydrogen: Obtained from high-purity hydrogen after dehydration and deoxygenation.

[0035] Unless otherwise specified, the pressures described in the present invention refer to gauge pressures.

[0036] Screening: The analysis was carried out using the ANALYSETTE 3SPARTAN analyzer from FRITSCH, with an amplitude of 2 mm and a vibration time of 15 min.

[0037] The catalyst is a supported catalyst prepared according to the method of Example 2 in CN103087241A.

[0038] Example 1

[0039] Polymerization of ethylene: The polymerization reaction of ethylene was carried out in a 10L autoclave reactor. Before adding materials, the dehydrated and deoxygenated polymerization autoclave was purged with nitrogen for at least 3 times, and then 5L of hexane dried by molecular sieve and nitrogen-bubbled was injected. After the temperature was raised to 50°C, 5mmol of triisobutylaluminum, 5mmol of diethylzinc, and 100mg of catalyst were added in sequence. Finally, 1L of hexane was added to flush the catalyst pipeline, and the reactor was heated again. After the temperature was raised to 80°C, ethylene was continuously added to make the ethylene partial pressure 1MPa, and the reaction was carried out at a constant pressure for 1 hour. After the polymerization was completed, the reactor was cooled and vented. After stirring for 10 minutes, the polymer slurry was recovered and the polymer powder was separated from the hexane.

[0040] The results of polymer screening and discharge weight are shown in Table 1.

[0041] Example 2

[0042] The method of Example 1 was followed, except that the amount of diethylzinc added was 8 mmol.

[0043] The results of polymer screening and discharge weight are shown in Table 1.

[0044] Example 3

[0045] The method of Example 1 was followed, except that the amount of diethylzinc added was 10 mmol.

[0046] The results of polymer screening and discharge weight are shown in Table 1.

[0047] Example 4

[0048] The method of Example 1 was followed, except that the amount of diethylzinc added was 20 mmol.

[0049] The results of polymer screening and discharge weight are shown in Table 1.

[0050] Example 5

[0051] The method of Example 1 was followed, except that the catalyst used in the polymerization was synthesized according to Example 1 of patent CN109694424B, and the weight used was the same.

[0052] Example 6

[0053] The method of Example 1 was followed, except that triisobutylaluminum was replaced with an equimolar amount of triethylaluminum as a cocatalyst.

[0054] Comparative Example 1

[0055] The method of Example 1 was followed, except that no diethyl zinc was added.

[0056] The results of polymer screening and discharge weight are shown in Table 1.

[0057] Comparative Example 2

[0058] The method of Example 1 was followed, except that "5 mmol of diethyl zinc" was replaced by "35 mg of an antistatic agent (Statsafe 6000)".

[0059] The results of polymer screening and discharge weight are shown in Table 1.

[0060] Comparative Example 3

[0061] The method of Example 1 was followed, except that 35 mg of an antistatic agent (Statsafe 6000) was added.

[0062] The results of polymer screening and discharge weight are shown in Table 1.

[0063] Table 1

[0064]

[0065] It can be seen from the results of Table 1 that the experimental results of Table 1 show that, compared with Comparative Example 1, after adding alkyl zinc, the particle size distribution of the polymer obtained after discharging is more concentrated, and the large particle size greater than 0.5 mm is significantly reduced. Compared with Comparative Examples 2 and 3, adding alkyl zinc without adding an antistatic agent can significantly improve the catalyst activity and the discharging amount, and at the same time, the large particle size greater than 0.5 mm is significantly reduced. Preferably, Examples 1-3 of the present invention can reduce polymer agglomeration while increasing the activity of the catalyst.

[0066] Meanwhile, the reactors of Examples 3-6 of the present invention can be observed to have only a small amount of agglomeration and flakes on the inner wall of the reactors, and preferably, the reactors of Examples 1-2 can be observed to have substantially no agglomeration and flakes on the inner wall of the reactors. However, the reactors of Comparative Examples 1-3 have obvious agglomeration and flakes on the inner wall.

[0067] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. The use of alkyl zinc in reducing polymer agglomeration in olefin polymerization, characterized in that: The application comprises: carrying out olefin polymerization in the presence of alkyl zinc and a catalyst; and no antistatic agent is used in the olefin polymerization process.

2. A method for reducing polymer agglomeration in olefin polymerization, characterized in that: The method comprises: carrying out olefin polymerization in the presence of alkyl zinc and a catalyst; and not using an antistatic agent during the olefin polymerization process.

3. The method or use according to claim 1 or 2, wherein: The alkyl zinc is at least one of C2-C10 alkyl zincs, preferably at least one of diethyl zinc, dimethyl zinc, dipropyl zinc and dibutyl zinc.

4. The method or use according to claim 1 or 2, wherein: The olefin polymerization is carried out in a polymerization medium, and the amount of alkyl zinc added is 0.1ppm-1000ppm of the polymerization medium; Preferably, the polymerization medium comprises an inert gas and / or a C3-C10 alkane.

5. The method or use according to claim 1 or 2, wherein: The catalyst is a supported catalyst, preferably at least one of a metallocene catalyst, a non-metallocene catalyst and a Ziegler-Natta catalyst; more preferably a supported metallocene catalyst.

6. The method or use according to claim 5, wherein: The metal element in the supported metallocene catalyst is at least one of the IVB elements, preferably at least one of Ti, Zr and Hf; More preferably, the supported metallocene catalyst comprises a bridged metallocene compound, an aluminoxane and a carrier; further preferably, the bridged metallocene compound has a structure of CpXCpMQ2, wherein Cp is a metallocene ligand, X is a bridging group, which is a C1-C4 carbon bridge, a silicon bridge or a germanium bridge with a substituted alkyl or cycloalkyl group; M is selected from at least one of the IVB elements; and Q is a halogen.

7. The method or use according to any one of claims 1 to 6, wherein: The olefin polymerization further comprises the use of a co-catalyst, wherein the co-catalyst is an organic aluminum, preferably, the organic aluminum is an alkyl aluminum, more preferably, the alkyl aluminum is selected from at least one of trimethyl aluminum, triethyl aluminum, tri-n-propyl aluminum, tri-isobutyl aluminum, tri-n-butyl aluminum, tri-isopentyl aluminum, tri-n-pentyl aluminum, tri-n-hexyl aluminum, tri-isohexyl aluminum, diethyl methyl aluminum and dimethyl ethyl aluminum.

8. The method or use according to claim 7, wherein: The molar ratio of the catalyst calculated as IVB element to the co-catalyst calculated as aluminum element is 1:10-5000, more preferably 1:25-2000.

9. The method or use according to any one of claims 1 to 8, wherein: The olefin is ethylene and / or α-olefin; preferably, the α-olefin includes at least one of propylene, 1-butene, 1-pentene, 1-hexene and 1-octene.

10. The method or use according to any one of claims 1 to 9, wherein: The conditions for olefin polymerization include: temperature 20-130°C, preferably 60-100°C; pressure 0.3-5MPa, preferably 0.5-3MPa; And / or, the olefin polymerization is carried out in a slurry polymerization or a gas phase polymerization.

Citation Information

Patent Citations

  • Method for preparing metallocene polyethylene

    CN103087241A

  • Catalyst component for ethylene polymerization, preparation method thereof and catalyst for ethylene polymerization

    CN109694424A

  • Catalyst components for ethylene polymerization and their preparation methods, and catalysts for ethylene polymerization.

    CN109694424B

  • Method for seed bed treatment for a polymerization reaction

    CN102257017A

  • Process for preparing homo-polypropylene from olefin monomer

    KR1020180033803A